Strategi Pemasaran Tenun Ulap doyo (Daun Lemba) Menggunakan Matriks SWOT (Studi Kasus pada UMKM Pokant Takaq) - Astik Drianti; Imas Nurmala (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2020)
Ulap Doyo Dayak Benuaq weaving is one of the characteristics of Kalimantan, especially East Kalimantan. Pokant Takaq is a UMKM which is a combination of several doyo weaving craftsmen in Tenggarong District. The purpose of this research is to identify internal and external conditions that affect the marketing of doyo weaving products and to find out alternative strategies that can be applied in the marketing of doyo weaving using SWOT analysis. To answer these two objectives, a SWOT analysis is used. This research was conducted at UKM Pokant Takaq, Tenggarong District, Kutai Kartanegara Regency in April-May 2020. The results of this study provide alternative strategies that can be applied, namely: a. Utilizing business permits to open outlets b. Maintaining product quality to meet export market demands, supported by distinctive colors and motifs. c. Take advantage of the government's role in the promotion and support of a dynamic marketing model. d. Utilizing information technology in the promotion of doyo weaving. e. Maintain good relationships with suppliers of raw materials and increase production.